Innovative Developments in Electro-Flocking Technology: An Advanced Study - Shlyakhtenko Pavel Grigorievich (Current Approaches in Science and Technology Research Vol. 10, 2021)
In a physically correct study of contact charging and trajectories of movement of short synthetic charged fibers in an inhomogeneous electric field, original results were obtained. Their comprehension led to the creation of a new theory of the formation of pile coverage. The use of the recommendations of this theory made it possible to develop a method for obtaining coatings, the surface density of the oriented pile of which is an order of magnitude higher than the maximum values attainable on the equipment existing in our country and abroad. Fundamentally new methods have also been developed for controlling the conductivity of the pile under conditions that are practically identical to the production conditions in which this parameter is used.